2005
DOI: 10.1038/sj.leu.2403809
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of RT-PCR-based quantification of WT1 gene expression during MRD monitoring of acute myeloid leukemia

Abstract: In search for general PCR targets for minimal residual disease (MRD) studies in acute myeloid leukemia (AML), Wilms' tumor gene 1 (WT1) expression was assessed by real-time RT-PCR relative to the control gene ABL in 569 archived samples of AML patients (pts). Pts were analyzed at diagnosis (n ¼ 116) and during follow-up (n ¼ 105, median 4 times, range 2-17). Median follow-up time was 258 days (range 16-1578 days). In 66 pts, the WT1 expression was analyzed in comparison to a second PCR marker or to multiparame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(123 citation statements)
references
References 31 publications
5
113
2
3
Order By: Relevance
“…These findings have been previously described and are in concordance with results of other studies. [47][48][49][50][51][52][53][54][55] WT1 isoform expression patterns showed at first glance subtle but significant differences among normal BM, AML and MDS, and also between childhood and adult samples. These specific patterns enabled the clustering of samples into groups representing the individual diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been previously described and are in concordance with results of other studies. [47][48][49][50][51][52][53][54][55] WT1 isoform expression patterns showed at first glance subtle but significant differences among normal BM, AML and MDS, and also between childhood and adult samples. These specific patterns enabled the clustering of samples into groups representing the individual diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] WT1 encodes a transcription factor that is involved in gonadal development. Mutations in WT1 were initially found to cause urogenital disease and kidney tumors, suggesting that it is a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Increased expression of WT1 is associated with unfavorable prognosis of multiple malignancies and its downregulation by different gene therapy strategies leads to a down of cell proliferation and apoptosis. [32][33][34][35] Overexpression of WT1 mRNA has been detected in 54 of 56 (96%) de novo non-small cell lung cancers and protein overexpression was confirmed in 5 of 6 (83%) de novo small cell lung cancers by immunohistochemistry. 43,44 It is therefore a target for gene therapy with high potential for lung cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the quantitative assessment of WT1 transcript allows to distinguish between normal and pathological samples, as well as increasing WT1 levels above the normal range can be prognostically significant during the follow-up of patients. Weisser et al (16), some years later, confirmed a significant correlation between WT1 levels and fusion genes (96%, median r = 0.996) in a similar study population. The authors also showed that more than 2 log reduction of WT1 levels within 61 and 180 days from the start of chemotherapy was associated with a significantly improved OS and event-free survival (EFS).…”
Section: Wt1 As a Minimal Residual Disease Marker After Conventional mentioning
confidence: 53%
“…On the contrary, a greater agreement was found among groups that have used WT1 levels as a marker of minimal residual disease (MRD) in AML remission BMs (less than 5% of blast cells). In particular, WT1 expression has been shown to predict disease progression in AML patients treated with conventional chemotherapy (8)(9)(10)(15)(16)(17) and patients undergone allogeneic stem cell transplantation (allo-SCT) (18)(19)(20)(21)(22). Furthermore, when WT1 expression was compared with widely used techniques in monitoring MRD such as multiparameter flow cytometry (MFC) (23) or specific molecular targets such as fusion genes transcripts (PMLRARa, AML-ETO1, and CBFb-MYH11), comparable sensitivities were found in predicting the relapse in AML.…”
Section: Introductionmentioning
confidence: 99%